Community Policing Enactment in Crime Prevention at South Jakarta - Santoso, Edi; Sumantri, Gumilar; Dharma, Surya; Purnomo, Hadi; Jha, Gautam Kumar; Insani, Nursolihi (Universitas Islam Negeri Madura, 2025)
Community policing, a proactive crime prevention strategy, faces unique challenges in apartment-based urban environments like South Jakarta's Kalibata City Apartment complex. These communities are characterized by higher levels of individualism and lower social cohesion, making it difficult to establish effective community-police partnerships. The study, involving 360 randomly selected residents, found that the social fabric of apartment communities lacks the integration necessary for successful community-policing partnerships. The study also highlighted the socio-spatial characteristics of apartment complexes, such as high population density and vertical living arrangements, which significantly shape the feasibility and outcomes of community policing initiatives. This research contributes to the broader discourse on urban policing by identifying key gaps in existing practices and emphasizing the need for context-sensitive approaches.